Manajemen Modal Intelektual: Strategi Memaksimalkan Nilai Modal Intelekstual dalam Technology Driven Business - Lina Anatan (Jurnal Manajemen Maranatha, 2006)
To date, there is a great deal changing in the way firm to compete. Over last decade, several driving force have emerge such as globalization of business and international competition sophisticated customers, competitor, and supplier increased technological capability, and shortening of production life cycle. Among the changes, knowledge management and intellectual capital management have probably made the most outstanding impact, the advent of the knowledge economy. Several characteristics define the knowledge economy are its focused on intangible resources rather than tangible resources, it’s has a hypercompetitive business environment, it’s digital, it’s virtual, and it’s networked. In the new knowledge economy, intellectual capital has has become the one and only competitive advantage of a firm. It’s include three dimension that is human capital, structural capital and customer capital. To implement strategy for managing intellectual capital successfully need to integrate the intellectual capital management strategies with the business strategy and to adapt internal and external changes.